The Phenomenon of Credit in Rural Communities (Case Study: Motorcycle Loans in the Nagari Gunung Padang Alai Community, Padang Pariaman Regency) - Erningsih, Erningsih (Universitas PGRI Sumatera Barat, 2024)
The inclusion of transportation to Nagari Gunung Padang Alai, Kecamatan V Koto Timur, Padang Pariaman Regency, has changed the perspective of community members to become more consumptive. Purchasing a motorcycle on credit was carried out. Motorbikes are used by community members as a means of transportation. This research was conducted with the aim to see the community's strategy to pay off motorcycle loan installments. This type of research is qualitative, namely research to produce descriptive data in the form of written or oral words from informants and their observed behavior. This type of research is a case study that is useful to highlight the life behaviors of individual groups. The research subjects were members of the public who bought motorcycles on credit, Wali Nagari, and the motorcycle credit management agency. The techniques used to obtain data are interviews, observation, and documentation